A Novel Technique of Stenting of the Renal Artery In-Stent Restenosis with GuideLiner® through Radial Approach - Maheedhar Gedela; Shenjing Li; Tomasz Stys; Adam Stys (Case Reports in Vascular Medicine)
In-stent restenosis of the renal arteries is relatively common and its management is not well studied. An 83-year-old female with bilateral renal artery stenosis and balloon angioplasty and stenting bilaterally one year ago was found to have recurrent severe elevations in the blood pressure despite medical management. Renal artery duplex showed 60–99% stenosis of the right renal artery and 20–59% stenosis of the left renal artery. A subsequent angiography of the right renal artery revealed 80% in-stent restenosis at the ostium. We describe a new approach of balloon angioplasty and stenting through radial access site with the assistance of a GuideLiner in a complex in-stent restenosis of the renal artery.